Modular Microfluidic Paper‐Based Devices for Multi‐Modal Cascade Catalysis. Issue 9 (2nd May 2019) - Andersen, Nalin I.; Artyushkova, Kateryna; Matanović, Ivana; Seow Chavez, Madelaine; Hickey, David P.; Abdelloui, Sofiene; Minteer, Shelley D.; Atanassov, Plamen
Abstract: The integration of different catalytic modalities to control precursors, intermediates, and products requires a method for understanding these complex systems. A modular analytical platform is presented here that allows for catalytic conversion reactions and the delivery of catalytically transformed analytes to subsequent surface enhanced Raman scattering (SERS) detection zones. The paper‐based platforms are compatible for studying biochemical conversion reactions and electrochemical transformations. The full oxidation of glycerol to carbon dioxide follows a cascade reaction of 9 steps, chosen to illustrate the use of a molecular, biological, and metallic catalyst. Designated catalytic reaction zones and SERS detection zones integrated into the pores of paper at specific locations allows all of the reactions to take place within the pores of the analytical platform. Multiple chemical reactions were performed in sequence and the SERS spectra of the resulting intermediates and products were measured. Abstract : Excuse me, SER(S) : Microfluidic 3D modular paper‐based analytical platforms equipped with stencil‐printed electrodes and SERS substrates are used to study multistep multimodal catalysis.